Leveraging small island context to advance and disseminate environmental health and sustainable development knowledge through higher education - Telesford, Lindonne; Nsobundu, Chinelo; Lewis, Tiffany; Marks, Aleah; Alamrany, Amran; Zaim, Oznur; Lachica, Innah; Eruaga, Allen; Roman, Lira Camille; Slavkovska, Tamara; Mandal, Dhruv; Chandran, Vijay (Frontiers in Education, 2024)
Higher education curricula can be designed to effectively leverage the context of small island states to enhance and deliver sustainable development and environmental health education, catering to workforce development, citizenry, and inclusivity. Small islands and developing states, in particular, are left behind in recognizing and promoting the linkages between environmentally sustainable development and the health of its people. This community case study highlights strategies of a Caribbean-based higher learning institution, leveraging the context of a small island state, to close this gap and create equitable access to integrated sustainable development and environmental health education. Tenets of Education for Sustainable Development theory underpin the pedagogical methodologies used in the delivery of the academic program. The curriculum draws on experiential learning, competency-based education, and diversity and inclusion, oriented to active student-student and student-practitioner engagements. Learning is facilitated through the effective dissemination of information, healthy interactions within a diverse community, professional engagements with multi-disciplinary practitioners, problem-solving, and formulation and presentation of perspectives and experiences relating to the Sustainable Development Agenda and Goals. Highly engaging and inclusive academic processes can accentuate students transitioning into the role of teachers, environmentally conscious leaders and citizens, and competent public health practitioners for the local and global workforces.